Research and Case Analysis of Ideological Education in Linear Algebra Courses under the OBE Concept - Zhan, Qiuyan; Chao, Lu (Journal of Educational Research and Policies, 2025)
With the gradual development and penetration of contemporary information technology in the field of education, the teaching mode of linear algebra courses is changing rapidly. In recent years, Outcome Based Education (OBE), as an advanced teaching model, has been increasingly accepted by many universities and implemented in the teaching reform and practice of linear algebra courses. This paper, based on the OBE educational concept and combined with the current teaching situation of linear algebra, proposes innovative teaching suggestions for ideological education in the linear algebra course group, aiming to improve the ideological education teaching system of Linear Algebra course groups under the OBE educational concept.